Novel antimicrobial and bioactive resin-based clear aligner attachment orthodontic materials - Alqarni, Heba; Ba-Armah, Ibrahim; Almutairi, Nader; Alenizy, Mohammad; Arola, Dwayne D.; Oates, Thomas W.; Sun, Jirun; Weir, Michael D.; Xu, Hockin H. K. (Frontiers in Oral Health, 2025)
IntroductionClear aligner orthodontic treatment provides a hygienic and esthetic alternative to fixed appliances; however, the required resin attachments can promote plaque accumulation and increase the risk of white-spot lesions in enamel. This study aimed to develop a novel resin-based antibacterial and bioactive orthodontic clear aligner attachment and evaluate its mechanical and antibacterial properties.MethodsA resin matrix composed of urethane dimethacrylate (UDMA) and triethylene glycol divinylbenzyl ether (TEG-DVBE) was modified with 3% dimethylaminododecyl methacrylate (DMADDM) for antibacterial effects and nano-amorphous calcium phosphate (NACP) to support remineralization. Transbond™ LV and Vitremer™ were selected as commercial controls. Mechanical properties (flexural strength, elastic modulus, microhardness, and shear bond strength), degree of conversion, and antibacterial performance against Streptococcus mutans (S. mutans) biofilms were assessed through colony forming units (CFU), biofilm metabolic activity (MTT), and lactic acid production.ResultsAll experimental groups showed flexural strength of 100.6–109.2 MPa, exceeding the ISO standard for resin-based materials. Degree of conversion in experimental groups ranged from (53.4 ± 2.3 to 69 ± 0.9) %, significantly exceeding (47.5 ± 0.1) % for Transbond control (p < 0.05). Hardness was (0.21 ± 0.03) GPa for Transbond control, statistically comparable to (0.20 ± 0.02) GPa for the 20% NACP + 45% glass group. All experimental groups achieved a 6-log reduction in biofilm CFU and 90% reduction in metabolic activity and lactic acid production vs. controls (p < 0.01).ConclusionThis novel clear aligner attachment resin exhibits promising mechanical strength, high degree of conversion, potent antibacterial effects, and ion releases to potentially reduce white-spot lesions during clear aligner treatment.